Factores bióticos y antibióticos de la finca del colegio técnico Vicente Anda Aguirre como potencial de desarrollo del cantón Pedro Vicente Maldonado. Año 2012. Propuesta de manejo ecoturístico - Velasco Chasi, Fausto Gonzalo (2013)
The present investigation, there carried out in the estate of the collage Vicente Anda Aguirre, Who is located in full head-board cantonal of Pedro Vicente Maldonado!s city, canton of the notwest of the province of bargain, to 608 msnm, withe an extension of hectares.